274 CUMULATIVE DOSES OF INDOMETHACIN AND CONCURRENT USE OF CORTICO-STEROIDS PREDICT SPONTANEOUS INTESTINAL PERFORATION IN THE VERY LOW BIRTH WEIGHT NEONATE. (10th December 2015) - Paquette, L.; Friedlich, P.; Ramanathan, R.; Seri., I.
Abstract : Introduction: Spontaneous intestinal perforation (SIP) occurs in 3.9-7.4% of very low birth weight (VLBW) neonates (birth weight [BW] ≤1500 g) during the first two postnatal weeks. Epidemiological data suggest that the use of corticosteroids and prostaglandin inhibitors predisposes VLBW neonates to an increase in the incidence of SIP. In this study, we tested the hypothesis that the concurrent use of indomethacin for the treatment of patent ductus arteriosus (PDA) and the use of postnatal steroids for the treatment of refractory hypotension increases the risk of SIP. Methods: In this 2:1 matched case-control study, the databases of two NICUs were queried for all infants with BW ≤1500 grams, admitted between 1997 and 2003. Infants with clinical and radiographic findings consistent with SIP without necrotizing enterocolitis by postnatal day 14 were selected as cases and matched to controls by BW. To assess the odds of SIP by clinically relevant variables, multivariate logistic regression analysis was performed using Stata/SE 8.0 (Stata Corporation College Station, TX). Results: Sixteen cases were matched to 32 controls. No significant differences in demographics were found between cases and controls. Mean BW and gestational age were 818 6 51 g and 835 6 37 g (p = 0.78) and 25.5 6 0.5 weeks and 26.0 6 0.4 weeks (p = 0.41), respectively. No differences in antenatal steroid use and prenatal maternal or fetal risk factors were noted. Neonates who received $ 3 doses of indomethacin and steroids were 9.6 times more likely to have SIP compared to infants who received ≤3 doses of indomethacin and steroids, after adjusting for gestational age, Apgar scores, presence of umbilical arterial lines, time of first stool, maximum inotropic needs and total cumulative dose of indomethacin and corticosteroids [95% CI 1.22 -75.71, p =0.032]. Conclusions: The combined use of indomethacin for closure of PDA and steroids for refractory hypotension during the first two postnatal weeks significantly increases the risks of SIP in VLBW neonates.